2020
DOI: 10.1108/jgoss-05-2019-0042
|View full text |Cite
|
Sign up to set email alerts
|

Cyber security risks in globalized supply chains: conceptual framework

Abstract: Purpose The purpose of this study is to examine cyber security risks in globalized supply chains (SCs). It has been seen to have a greater impact on the performance of SCs. The information and communication technology of a firm, which enhances the efficiency and effectiveness in the SC, could simultaneously be the cause of vulnerabilities and exposure to security threats. Researchers have primarily focussed on the cyber-physical system (CPS) vulnerabilities impacting SC. This paper tries to categorize the cybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 83 publications
(105 reference statements)
0
58
0
3
Order By: Relevance
“…These systems make it necessary to analyze Cybersecurity risks in a globalized Supply Chain. Some occur due to cyber-attacks that cause an operational disruption in the SC; others cause an operational disruption affecting the entire Supply Chain, and others are produced by an inappropriate interaction between man and machine [ 55 ]. In addition to Cybersecurity, security in the traceability of operations is also necessary, for which a reference architecture of the applicability of Blockchain technology is necessary as well [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…These systems make it necessary to analyze Cybersecurity risks in a globalized Supply Chain. Some occur due to cyber-attacks that cause an operational disruption in the SC; others cause an operational disruption affecting the entire Supply Chain, and others are produced by an inappropriate interaction between man and machine [ 55 ]. In addition to Cybersecurity, security in the traceability of operations is also necessary, for which a reference architecture of the applicability of Blockchain technology is necessary as well [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the elements, much of the focus for research still appears to be on cyber risks, sources of cyber risks and measures to tackle them. Previous contributions mainly present conceptual frameworks without empirical data (Boyson, 2014;Radanliev et al, 2020), investigations with illustrative cases or on companies working in different supply chains (Urciuoli and Hintsa, 2017;Pandey et al, 2020) or modelling efforts on specific issues or risk events (Deane et al, 2009;Li and Xu, 2020). The only contributions on the evaluation of perceptions within the investigated field focus either on the effect of incident awareness on information security policies (Volpentesta et al, 2011) or on perceptions of risks and IT interventions (Gaudenzi and Siciliano, 2017) but without embracing cyber risks according to a supply chain perspective.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Consequently, it appears that the industrial and scientific communities are concentrated on trying to make sense of "what can be done" to deal with cyber and information risks in the supply chain, particularly at the IT security level within the boundaries of the single organizations, without focusing first on the elements constituting a supply chain security strategy. Developing a fully integrated strategic approach to cyber risk is fundamental to supply chains and to think about how to address cyber risk at the end of the strategic process is simply too late in a cyber supply chain management process (Pandey et al, 2020). These elements also constitute the pillars for creating alignment in the supply chain regarding what kind of policies, actions and initiatives should be undertaken to secure the entire supply chain, rather than protecting only single organizations, which by themselves can become individual points of failure in cyberspace.…”
Section: Introductionmentioning
confidence: 99%
“…11 Pandey and Singh describe a range of methods of attacking supply chain systems, from pre-installed malware on manufacturer components, to Denial of Service (DoS) attacks compromising availability of resources, direct attacks to damage and destroy services and, in particular, the ease of initial attacks against a thirdparty enabling access to their ultimate target. 12 A global supply chain survey by BlueVoyant reported that 80 % of participants had experienced a third-party breach during the past year and 77 % have limited visibility of their supply chain, with only 2 % managing to monitor their vendors in real time or daily. The energy system is becoming more distributed with an increasing reliance on third parties.…”
Section: Supply Chain Compromisesmentioning
confidence: 99%